Serie A, Nr. 23; Bruno Heck:"das Leben im Stadion ist bei sonnigen Wetter recht angenehm" - Staeck, Klaus, (1974)
Serie A, Nr. 23; Bruno Heck:"das Leben im Stadion ist bei sonnigen Wetter recht angenehm".